DEVELOPING POSITIVE ATTITUDES TOWARDS NON-EUCLIDEAN GEOMETRY: https://doi.org/10.5281/zenodo.14235553 - Abdullah , Kurudirek; Zarekeeva , M; Yuldasheva , F; Mirzabaeva , U (International scientific and practical conference, 2024)
This paper describes one teacher's attempts to teach critical geometry understandings to a Grade 11 class in methods that interest students and help them advance positive impressions of their capacity to master basic ideas of non-Euclidean geometries in a rigorous and symbolic way [1,2,3]. This study offers a four-week geometry intervention that connects concrete representations with symbolic expressions and figures by carefully using formal geometry language. The teacher expressed his hope that interventions like this will motivate more students to pursue advanced geometry courses in college.The study gathered information on student perceptions of their learning experiences, including impressions of non-Euclidean geometries as a subject domain, participation in activities, geometric understanding development, and classroom discourse quality. This study discovered that students appreciated classroom conversation far more than they did traditional geometry learning activities. Besides these findings have ramifications for both in-service and pre-service teacher education.